Profil Petani Bunga Teratai di Subak Duaji, Desa Sibanggede, Kecamatan Abiansemal, Kabupaten Badung, Bali - SANJAYA, GEDE DELIN; SUSRUSA, KETUT BUDI; ARISENA, GEDE MEKSE KORRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Profile of Lotus Flower Farmers in Subak Duaji, Sibanggede Village, Abiansemal Sub-District, Badung Regency of Bali Province The rapid development of lotus flower plantations in Subak Duaji is certainly very influential on the parties involved in the management of farming, namely farmers. The success of farmers can be measured by the ability of farmers to manage their farms. The motivation behind this examination is to analyze the profile of lotus flower farmers through inside and outside qualities of farmers, farmers income and the obstacles faced by farmers. The research was conducted in Subak Duaji, Sibanggede Village with 53 respondents. The analytical method used is descriptive quantitative and qualitative analysis. The results of the analysis show that the land is managed by the farmers themselves, with family labor, the capital comes from the farmers themselves, with their own agricultural tools and machines, the age of the lotus farmer is the production level, the number of dependents in the family is less than 3 people, the education level is high school, the average area of land is 30.4 acres, have experience in farming between 5-10 years. There is no counseling to lotus farmers, information and communication media are obtained between farmers, the role of the government is available, with flower marketing done by direct marketing to consumers. The average net income of farmers from lotus farming is IDR 18.067.751/30.4 Are/year. Constraints faced by farmers are the lack of water availability during irrigation improvements upstream, the lack of consumers to buy lotus flowers on the day and the constraints of the presence of pests that attack plants. This farming is quite profitable.